Aptamer-Driven Toxin Gene Delivery in U87 Model Glioblastoma Cells - Luana di Leandro; Francesco Giansanti; Sabrina Mei; Sara Ponziani; Martina Colasante; Matteo Ardini; Francesco Angelucci; Giuseppina Pitari; Michele d'Angelo; Annamaria Cimini; Maria Serena Fabbrini; Rodolfo Ippoliti (Frontiers Media S.A., 2021)
A novel suicide gene therapy approach was tested in U87 MG glioblastoma multiforme cells. A 26nt G-rich double-stranded DNA aptamer (AS1411) was integrated into a vector at the 5' of a mammalian codon-optimized saporin gene, under CMV promoter. With this plasmid termed "APTSAP", the gene encoding ribosome-inactivating protein saporin is driven intracellularly by the glioma-specific aptamer that binds to cell surface-exposed nucleolin and efficiently kills target cells, more effectively as a polyethyleneimine (PEI)-polyplex. Cells that do not expose nucleolin at the cell surface such as 3T3 cells, used as a control, remain unaffected. Suicide gene-induced cell killing was not observed when the inactive saporin mutant SAPKQ DNA was used in the (PEI)-polyplex, indicating that saporin catalytic activity mediates the cytotoxic effect. Rather than apoptosis, cell death has features resembling autophagic or methuosis-like mechanisms. These main findings support the proof-of-concept of using PEI-polyplexed APTSAP for local delivery in rat glioblastoma models.